Możliwości i perspektywy ekumenicznej posługi duchownych wobec chorych w warunkach hospitalizacji - Froniewski, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The paper shows the range of possibilities of ecumenical service of priests to the sick of other Christian denominations. In Poland it is a problem which has been growing in the face of contemporary migration movements. Nowadays the chaplain in his service in hospitals much more often encounters the faithful of other denominations. Also medical science clearer and clearer sees in patients care a whole range of determinants linked to their denomination, on which often depends their perception of the quality of medical services they are offered. On the other hand, the knowledge on this subject continues to be little, and still quite often prejudices can be encountered which have been developing historically. Because of the peculiarity of the Polish conditions, where Catholicism is the predominant denomination, the starting point for developing the question will be determinants resulting from the canon law, which define from the Catholic side the range of possible service to the sick of other denominations. Also a synthesis of respective possibilities from the Orthodox and protestant sides will be presented. Next, by means of an analysis of liturgical books, the most appropriate forms of the priest service to the sick which are possible on the ecumenical ground will be indicated and prospects of their development outlined
Keywords: ekumenizm; posługa chorym; namaszczenie chorych; kapelan szpitalny; medycyna; usługi; prawo kanoniczne